A new family of reduced models for non-isothermal falling films. (June 2020) - Cellier, Nicolas; Ruyer-Quil, Christian
Highlights: Innovative approach based on a clever parametrization and use of relaxation modes. Extension of modeling of heat transfer across a film up to large values of Pe number. Design of an efficient tool enabling costly investigations (optimization etc.). Abstract: New asymptotic models are formulated to capture the thermal transfer across falling films. These models enable us to simulate a wide range of Biot and Peclet number values, without displaying nonphysical behaviors. The models correctly capture the onset of the thermally developed regime at the inlet of the flow. To evaluate the parameter space of acceptability, a comparison has been made with the primitive equation solution for periodic boundary conditions, as well as for an open flow with a periodic forcing at the inlet. A good agreement is obtained for moderate to high Peclet numbers.